2009
DOI: 10.1007/s00436-009-1387-z
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma japonicum: proteomics analysis of differentially expressed proteins from ultraviolet-attenuated cercariae compared to normal cercariae

Abstract: Schistosomiasis is considered the most important human helminthiasis in terms of morbidity and mortality. In this study, comparative soluble proteomic analysis of normal cercariae and ultraviolet-irradiated attenuated cercariae (UVAC) from Schistosoma japonicum were carried out in view of the high efficiency of irradiation-attenuated cercariae vaccine. The results revealed that some proteins showed significant differential expression in the parasite after treatment with ultraviolet light. Total 20 protein spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…The landmark availability of the complete sequences of the S. japonicum (171) and S. mansoni (18) genomes will provide the necessary ancillary information. As well, new approaches in antigen discovery through the generation of a large schistosome transcriptome database, gene finding, and the explosion in postgenome technologies, including DNA microarray profiling, proteomics, glycomics, immunomics, and the application of RNA interference (RNAi) and novel imaging techniques (2,24,25,41,53,72,73,75,76,85,95,109,126,127,179,189,197,205,219,224,230), provide an unprecedented opportunity to identify a new generation of vaccine target molecules that may induce greater potency than the current candidate schistosome antigens (138).…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…The landmark availability of the complete sequences of the S. japonicum (171) and S. mansoni (18) genomes will provide the necessary ancillary information. As well, new approaches in antigen discovery through the generation of a large schistosome transcriptome database, gene finding, and the explosion in postgenome technologies, including DNA microarray profiling, proteomics, glycomics, immunomics, and the application of RNA interference (RNAi) and novel imaging techniques (2,24,25,41,53,72,73,75,76,85,95,109,126,127,179,189,197,205,219,224,230), provide an unprecedented opportunity to identify a new generation of vaccine target molecules that may induce greater potency than the current candidate schistosome antigens (138).…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…It has been shown that detection of schistosome circulating antigen (CA) is an effective approach to discriminate between previous exposure and current infection (Zhu 2005). There were many reports showing that 14-3-3 of S. japonicum was abundant in excretory-secretory antigen ), soluble egg antigen (Yang et al 2009) and adult worm antigen , and has an important value in diagnosis of acute and chronic infections of Schistosoma japonicum (Luo et al 2009); however, the kinetics of 14-3-3 in the sera of rabbits infected with S. japonicum and then treated with praziquantel remains unclear. The current study, therefore, was carried out to explore its dynamic changes.…”
Section: Introductionmentioning
confidence: 99%
“…As snail control is always difficult to achieve [6], and treatment with praziquantel does not prevent a high frequency of reinfection [7], schistosomiasis is difficult to control. Thus, to control this disease, there is an urgent need to develop alternative therapies and effective vaccines [8] that could reduce the release of eggs and restrict parasite transmission or induce which kind of activity against schistosome infection.…”
Section: Introductionmentioning
confidence: 99%